Effect of smartphone application-supported self-rehabilitation for frozen shoulder: a prospective randomized control study. (April 2019) - Choi, Younggeun; Nam, Jihoon; Yang, Dongseok; Jung, Whanik; Lee, Hwa-Ryeong; Kim, Sae Hoon
Objectives: To evaluate the clinical efficacy of smartphone-assisted self-rehabilitation in patients with frozen shoulder. Design: A single-center, randomized controlled trial. Setting: Orthopedic department of a university hospital. Subjects: A total of 84 patients with frozen shoulder were recruited. Intervention: Patients were randomly divided into two groups: a smartphone-assisted exercise group ( n = 42) and a conventional self-exercise group ( n = 42). The study was performed over three months, during which each group performed home-based rehabilitation. Main measures: Visual analogue scale for pain and passive shoulder range of motion were assessed at baseline and after 4, 8, and 12 weeks of treatment. Technology Acceptance Model–2 and Usefulness, Satisfaction, and Ease of Use scores were evaluated in the smartphone group. Results: Initial visual analogue scale for pain of the smartphone group was 6.0 ± 2.2 and ended up with 1.8 ± 2.5 after 12 weeks, whereas the self-exercise group showed 5.8 ± 2.3 for the baseline visual analogue scale for pain and 2.2 ± 1.7 at the end. Significant time-dependent improvements in all measured values were observed in both groups (all P s < 0.001), but no significant intergroup difference was observed after 4, 8, or 12 weeks of treatment. In the smartphone group, Technology Acceptance Model–2 and Usefulness, Satisfaction, and Ease of Use scores showed high patient satisfaction with smartphone-assisted exercise. Conclusion: There was no difference between home-based exercise using a smartphone application and a conventional self-exercise program for the treatment of frozen shoulder in terms of visual analogue scale for pain and range of motions.